The Effect of Attribute Performance and Corporate Brand Image on Retention and Willingness to Pay Premium Prices In Energy Logistics Service Providers In Indonesia - Rendi Andika Saputro; Rifelly Dewi Astuti (Green Publisher Indonesia, 2025)
This study explores the mediating role of corporate brand image on the impact of logistics performance attributes on customer retention and their willingness to pay a premium in the Indonesian energy logistics industry. Addressing the scarcely researched intricacies of energy logistics services in Indonesia, this research aims to fill a gap by examining the specific role of corporate brand image in Business-to-Business (B2B) relationships, which has been more extensively studied in other national contexts such as China. Data generated from 30 companies whose the client of one big logistic company in Indonesia, and the data analyzed by SEM-PLS. Findings indicate that the corporate brand image exerts a positive and significant influence on customer retention, yet it does not significantly affect the willingness to pay a premium. Logistics performance attributes demonstrated a positive and significant impact on both variables, customer retention) and premium pricing. There was also a significant influence of logistics performance attributes on corporate brand image. The study reveals that the corporate brand image partially mediates the relationship between logistics performance attributes and willingness to pay a premium, but not in the case of customer retention. These insights are vital for energy logistics companies in Indonesia to enhance brand image strategies to improve retention and customer willingness to pay more.